An S-curve efficient frontier on second-hand auto price. (3rd February 2023) - Salim, Fadzilah; Abu, Nur Azman
An efficient frontier has been a popular concept in a capital asset pricing model in the last 50 years. An efficient frontier will be explored as a practical predictive model for second-hand automobile prices. It is a practically useful model that comes with an upper price recommendation on the market to suggest maximum possible coverage by auto insurance. A nonlinear model has been observed to give a better estimate of price appreciation while describing real-life phenomena. In this paper, an S-efficient frontier curve model is proposed as a simple nonlinear model used for estimating second-hand automobile pricing. A dynamic S-shaped membership function (SMF) will be used as a basis to construct an S-curve algorithm in this automobile price model. An S-curve model is found to offer a useful and practical estimation regarding second-hand auto prices. Therefore, an S-curve efficient frontier model along automobile make years is expected to provide a better estimate of second-hand auto pricing in Malaysia.